2019
DOI: 10.21203/rs.2.14052/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV screening in men and women in Senegal: coverage and associated factors analysis of the 2017 demographic and health survey

Abstract: Introduction Despite the adoption of the provider-initiated HIV testing strategy, the rate of HIV testing is still very low in sub-Saharan Africa. The aim of this study was to assess the factors associated with HIV testing among in sexually active women and men in Senegal. Knowledge of HIV status is the gateway to antiretroviral treatment.Methods A secondary analysis of the 2017 Senegal Demographic and Health Survey (DHS) was performed, using data on sexually active women age 15-49 and men age 15-59. The outco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
4
0
0
Order By: Relevance
“…The odds of getting HIV tests for Ethiopian youths with middle and rich wealth status were nearly 1.28 and 1.72 times higher compared to their poor peers. This finding is similar to the results of many other studies done in Southeast Asia and Africa where youths from households in the highest wealth quintile were more likely to opt-in for HIV testing as compared to youths from households in the poor wealth quintile [ 31 , 33 , 41 , 42 ]. This can be explained by differences in access to media and access to health facilities for rich people than poor people.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The odds of getting HIV tests for Ethiopian youths with middle and rich wealth status were nearly 1.28 and 1.72 times higher compared to their poor peers. This finding is similar to the results of many other studies done in Southeast Asia and Africa where youths from households in the highest wealth quintile were more likely to opt-in for HIV testing as compared to youths from households in the poor wealth quintile [ 31 , 33 , 41 , 42 ]. This can be explained by differences in access to media and access to health facilities for rich people than poor people.…”
Section: Discussionsupporting
confidence: 90%
“…For married youths and youths with another form of marital status, the odds of getting HIV tests were nearly 5.37 and 4.60 times higher compared to their peer youths who are not in marital union. Studies from Cambodia, Malawi, Tanzania, and Senegal using secondary DHS data analyses also showed that ever-married women more likely accept HIV testing as compared to never-married women which are consistent with the findings from the current study [ 30 , 33 , 41 , 56 ]. There could be different possible reasons for this.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations